2017
DOI: 10.1002/2017gl075661
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Geothermal Heat Flux in Greenland: A Machine Learning Approach

Abstract: Geothermal heat flux (GHF) is a crucial boundary condition for making accurate predictions of ice sheet mass loss, yet it is poorly known in Greenland due to inaccessibility of the bedrock. Here we use a machine learning algorithm on a large collection of relevant geologic features and global GHF measurements and produce a GHF map of Greenland that we argue is within ∼15% accuracy. The main features of our predicted GHF map include a large region with high GHF in central-north Greenland surrounding the NorthGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 29 publications
6
90
2
Order By: Relevance
“…This is because these regions tend to exhibit a diffuse scattering signature (associated with fine-scale roughness), whereas the method proposed by Gogineni (2008, 2012) is specifically tuned to detect water bodies that exhibit a spatially continuous (near-) specular scattering signature. By contrast, comparison between the water predictions in this study and the radar-derived bed roughness maps in Rippin (2013) and Jordan et al (2017) demonstrate a lack of modulation by bed roughness, with basal water present in rougher marginal regions and a generally smoother ice-sheet interior.…”
Section: Comparison With Past Res Analyses Of Basal Water and Disruptcontrasting
confidence: 88%
“…This is because these regions tend to exhibit a diffuse scattering signature (associated with fine-scale roughness), whereas the method proposed by Gogineni (2008, 2012) is specifically tuned to detect water bodies that exhibit a spatially continuous (near-) specular scattering signature. By contrast, comparison between the water predictions in this study and the radar-derived bed roughness maps in Rippin (2013) and Jordan et al (2017) demonstrate a lack of modulation by bed roughness, with basal water present in rougher marginal regions and a generally smoother ice-sheet interior.…”
Section: Comparison With Past Res Analyses Of Basal Water and Disruptcontrasting
confidence: 88%
“…Rogozhina et al () reconstructed a broad band of enhanced geothermal flux, exceeding 80 mW/m 2 , extending from east Greenland including Scoresby Sund, running northwest and passing just north of the GISP2 and GRIP ice core sites to include the NorthGRIP and NEEM sites. Rezvanbehbahani et al () and Rysgaard et al () estimated high geothermal fluxes (using global statistics together with the mapped features in Greenland, and using fjord temperatures, respectively), which broadly agree with the reconstructions of Rogozhina et al (). The seismic inversions of Pourpoint et al (2018) yielded widespread deep‐crustal low‐velocity anomalies in north and northeast Greenland that may be compositional but also may be thermal, broadly consistent with the other results.…”
Section: Geologic Settingmentioning
confidence: 54%
“…Rogozhina et al () estimated that GHF values range between 68 and 88 mW/m 2 in NEG and that the largest anomaly is located beneath the onset of NEGIS where high basal melting has been estimated (Fahnestock et al, ). In addition, GHF values ranging from 90 to 160 mW/m 2 have been estimated around the NorthGRIP ice core site (Buchardt & Dahl‐Jensen, ; Dahl‐Jensen, Gundestrup, et al, ; Greve, ; Rezvanbehbahani et al, ). A recent study by Rysgaard et al () also reported a GHF of 93 mW/m 2 in the Young Sound‐Tyrolerfjord, a few degrees south of the strong gravity low, and suggested, based on the distribution of high GHF, that a geothermal heat source may exist beneath the central and northeastern parts of the GIS.…”
Section: Resultsmentioning
confidence: 99%